PROSPECTS FOR THE INTRODUCTION OF INFORMATION SECURITY IN THE MANAGEMENT OF SOCIAL SERVICES - Yarova , Yu.М. (The actual problems of regional economy development, 2025)
The article discusses the prospects of introducing information support into the activities of social services. Modern challenges in the management of the social sphere are analyzed and the key advantages of using information and communication technologies are determined. Prospects for the development of information support in the social sphere are considered. Social services work with huge amounts of information that require efficient storage, processing and analysis. The lack of a single information platform creates difficulties in cooperation between different social services. Information provision is the basis of effective management in the social sphere. In the conditions of rapid technological evolution, it is especially important to ensure high-quality data collection, their processing and analysis for making management decisions. Information support for the management of social services is a system of collecting, processing, storing and transmitting information that is used for the effective functioning of social institutions. It includes information systems, databases, electronic document flow and digital platforms that help automate work. Information provision is a key element in the reform of social services, impairs the improvement of the efficiency of their work, the expansion of access to social services and the improvement of the quality of service to citizens. However, successful implementation requires a comprehensive approach that includes technology upgrades, staff training, and cyber security. Modern technology development opens up new opportunities for effective management of social services. Information provision is becoming an integral part of the modernization of state administration and provision of social protection of the population. This allows not only to optimize management processes, but also to create a transparent system of interaction between state institutions, citizens and public organizations. The purpose of the article is to study the theoretical aspects of modern trends and the prospect of introducing information support in the management of social services. The research was conducted using such research methods as the method of scientific abstractions, the method of comparison and economic analysis and synthesis. Information support plays a crucial role in improving decision-making processes within the framework of social work management. Effective decision-making is largely dependent on accurate and up-to-date information that enables social workers to assess situations, identify needs and determine appropriate interventions. Improving service delivery and outcomes for clients is another significant benefit of reliable information provision in social work management. Access to accurate and timely information allows social workers to tailor interventions that meet the specific needs of clients, thereby increasing the effectiveness of social services. Information sharing promotes transparency and a collaborative culture, allowing professionals to coordinate efforts and align their strategies.